Structure of the Students' Professional Subject Position in Governorate College - N I Matveyeva (Peoples' Friendship University of Russia (RUDN University), 2011)
The article describes the aspects and the structure of professional subject position of the students of a provincial college; the technological and qualitative changes in training middle managers to work in agricultural production; value-professional component as a basis for the formation of professional subject position.